(untitled) (Comprehensive Journal of Science, 2025)
This study aims to analyze the impact of quality of work life on employee job performance. It examines factors that contribute to improving the work environment and raising employee satisfaction, such as work-life balance, working conditions, rewards and motivation, and opportunities for career growth and development. The study focuses on assessing how quality of work life impacts employee commitment, productivity, and internal motivation, as it is an essential element for achieving outstanding performance and fulfilling the organization’s strategic objectives. The results revealed: Quality of work life is a directly influential factor in enhancing job performance by increasing employee satisfaction and job commitment. A supportive work environment and work-life balance programs contribute to increasing employee creativity and motivation. Job performance is closely linked to the extent to which an organization adopts clear policies to improve working conditions and provide professional development opportunities. Organizations face challenges related to the lack of sufficient resources to improve the work environment and the weakness of employee support programs. This requires the adoption of effective strategies to enhance quality of work life and achieve outstanding and sustainable performance.